2015
DOI: 10.1371/journal.pone.0117748
|View full text |Cite
|
Sign up to set email alerts
|

Low Maternal Vitamin D Status during the Second Trimester of Pregnancy: A Cross-Sectional Study in Wuxi, China

Abstract: BackgroundVitamin D deficiency is common in pregnant women, but an optimal serum vitamin D level during pregnancy has not been determined and remains an area of active research. Vitamin D data from large populations of pregnant Chinese women are still limited.ObjectiveTo evaluate the vitamin D status of women in Eastern China during the second trimester of pregnancy.MethodsA hospital-based, cross-sectional, observational study. Serum 25-hydroxyvitamin D [25(OH)D] concentration was measured in samples from 5823… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 26 publications
(27 reference statements)
3
43
2
Order By: Relevance
“…Contrary to the study results from the USA and China, we found that vitamin D levels in younger pregnant women (<30 years) were higher than in older ones (≥30 years) [35,36]. Although the results may be biased by the small size of the studied group, we may hypothesize that younger women have a longer sun exposure, and they comply more likely with prenatal care recommendations, such as folic acid supplementations, which might simultaneously contain vitamin D; the isolated vitamin D supplements during pregnancy is currently an infrequent clinical practice in Slovenia.…”
Section: Discussioncontrasting
confidence: 98%
“…Contrary to the study results from the USA and China, we found that vitamin D levels in younger pregnant women (<30 years) were higher than in older ones (≥30 years) [35,36]. Although the results may be biased by the small size of the studied group, we may hypothesize that younger women have a longer sun exposure, and they comply more likely with prenatal care recommendations, such as folic acid supplementations, which might simultaneously contain vitamin D; the isolated vitamin D supplements during pregnancy is currently an infrequent clinical practice in Slovenia.…”
Section: Discussioncontrasting
confidence: 98%
“…This observation could be supported by earlier findings showing varying 25(OH)D concentrations in mothers and their children [35,38,39,40]. Our study did not collect data on risk factors influencing 25(OH)D concentrations in the population, including clothing habits, outdoor activities, and dietary habits.…”
Section: Discussionsupporting
confidence: 82%
“…Women who either did not use vitamin D supplementation or stopped supplementation after early pregnancy were younger, less-well educated, more likely to smoke, and less likely to be in their first pregnancy and had higher prepregnancy BMI. Previous cross-sectional studies have identified that younger age (19), higher BMI or weight (20)(21)(22), smoking (6,(20)(21)(22), and lower educational achievement (20) increase risk of vitamin D deficiency in pregnancy, whereas a higher parity is protective (22). Although the majority of women in this study were pregnant before the publication of the United Kingdom Department of Health guidelines that suggest that all women should receive vitamin D supplementation in pregnancy (9), similar demographic factors have also been associated with a reduced likelihood of folic acid supplementation during pregnancy (23,24).…”
Section: Maternal Determinants Of Change In Season-corrected 25(oh)dmentioning
confidence: 95%